Peran Konselor dalam Mengatasi Stres Akademik dan Konflik Sosial pada Siwa - Tamam, Safira Putri (Maliki Interdisciplinary Journal, 2025)
This research addresses the importance of the counselor’s role in managing academic stress and social conflict among students. Academic stress, which results from academic pressure, can negatively impact students’ mental health and achievement. Counselors serve as mediators in resolving social conflicts and provide guidance to help students recognize their potential. Through preventive approaches and appropriate interventions, counselors can create a more harmonious learning environment and support students’ overall development. This research also suggests the need for longitudinal studies to evaluate the impact of stress on mental health and academic achievement, as well as the development of effective intervention programs. Thus, this study emphasizes the importance of mental health support in the educational context to improve student well-being and the effectiveness of guidance and counseling services in schools.